OpenICPSR. Issue 5 (19th June 2014) - Lyle, Jared
Abstract: EDITOR'S SUMMARY The University of Michigan has added an option for researchers who want to self‐publish research data. As a variation on the 50‐year old Inter‐university Consortium for Political and Social Research data archive, the University has launched openICPSR allowing rapid data deposit and public access at no cost or minimal charge. Like the long‐standing archive, the openICPSR focuses on social and behavioral science and enjoys the sponsorship of an established university. It offers immediate distribution to 750 other institutions, an easy‐to‐use interface, topic‐specific metadata applied automatically and reviewed by professionals in the field and the capacity to handle restricted use data. Data may also be published in the standard archive. Social and behavioral scientists should consider archive features, preservation needs, audience and any disclosure risks when selecting a channel to self‐publish their research data.